A Comparative Analysis to Determine Clinical Factors Influencing Technicity Index Between Hospitals [3J]. (May 2016) - Pelinska, Gabriela; Vilayil, Ruth; Chehade, Rania; Baird, Jennifer; Schulz, Jane; Brown, Ronald
Abstract : INTRODUCTION: Canadian national guidelines recommend minimally invasive hysterectomy as the preferred route due to less complications and shorter hospital stays. An index known as Technicity quantifies the number of minimally invasive hysterectomies relative to the total performed annually. Our aim was to compare a tertiary care and community hospital to determine factors leading to differences in Technicity Index (TI). METHODS: We reviewed all hysterectomies performed at Royal Alexandra Hospital (RAH—tertiary care), and Grey Nun's Hospital (GNH—community) in Edmonton, Alberta, Canada in 2011. There were 1, 053 charts reviewed. We collected data regarding type of procedure, patient BMI, number of medical and surgical comorbidities, length of hospital stay, and complication rate. RESULTS: Compared to abdominal and vaginal hysterectomy (AH, VH), the laparoscopic approach was associated with shorter hospital admission (1.8 days versus 2.5 days for AH and VH). With laparoscopic hysterectomy (LH), blood loss was decreased and patients were less likely to need a blood transfusion (AH [8%], VH [2%], LH [1%]). The TI was significantly increased at the community hospital (GNH 48.2%) compared to the tertiary care hospital (RAH 23.7%) ( P <.001). The patients treated at RAH had a greater number of medical (3.0 [RAH] versus 1.9 [GNH]) and surgical (2.2 [RAH] versus 1.2 [GNH]) comorbidities and higher BMI (30.4 versus 29.0). CONCLUSION: The benefits of minimally invasive hysterectomy are supported in this study. Differences in patient demographics such as BMI, medical and surgical comorbidities may influence the percentage of minimally invasive hysterectomies performed at an institution.